2023
DOI: 10.1186/s12886-023-02932-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of tear film breakup time with a novel smartphone-attachable technology

Abstract: Purpose To demonstrate the practicability of a portable instrument in assessing tear film breakup time (TFBUT): a lens attachment for smartphones (LAS). Methods By applying LAS in combination with the iPhone 12 pro, and a recordable slit-lamp microscope, we obtained TFBUT videos from 58 volunteers. The comparison between the conventional slit-lamp microscope and LAS by an experienced ophthalmologist. Moreover, we also invited an ophthalmic postgrad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Another study by Zhang et al also reported high agreement for measurement between an undergraduate student and a postgraduate student was 0.864 (95% CI, 0.810-0.904), between an undergraduate student and an ophthalmologist, was 0.922 (95% CI, 0.889-0.945), between a postgraduate student and an Ophthalmologist was 0.949 (95% CI, 0.927-0.964), and the average was 0.911 (95% CI, 0.881-0.934), the mean was 0.911 (95% CI, 0.881-0.934), using the same technology called Lens Attachment for Smartphone. 23 Based on two studies by Shimizu et al, we decided to do further research using SEC as novel inventions in Ophthalmology technology and this is the pilot study in populations-based research using SEC in diagnosis of DED in Indonesia. 7,11 This current study showed good consistency between interobservers (ophthalmologist and nonophthalmologist) in assessing TBUT examination (mean difference=0.78; 95% CI=−0.26-1.84; p=0.143), and DED detection (kappa coefficient = 0.71).…”
mentioning
confidence: 99%
“…Another study by Zhang et al also reported high agreement for measurement between an undergraduate student and a postgraduate student was 0.864 (95% CI, 0.810-0.904), between an undergraduate student and an ophthalmologist, was 0.922 (95% CI, 0.889-0.945), between a postgraduate student and an Ophthalmologist was 0.949 (95% CI, 0.927-0.964), and the average was 0.911 (95% CI, 0.881-0.934), the mean was 0.911 (95% CI, 0.881-0.934), using the same technology called Lens Attachment for Smartphone. 23 Based on two studies by Shimizu et al, we decided to do further research using SEC as novel inventions in Ophthalmology technology and this is the pilot study in populations-based research using SEC in diagnosis of DED in Indonesia. 7,11 This current study showed good consistency between interobservers (ophthalmologist and nonophthalmologist) in assessing TBUT examination (mean difference=0.78; 95% CI=−0.26-1.84; p=0.143), and DED detection (kappa coefficient = 0.71).…”
mentioning
confidence: 99%